PERAN KELUARGA DALAM PENDIDIKAN AGAMA ISLAM - Surur, Miftahus; Kamilah, Siti (Raudhah - Proud To Be Professional, 2025)
The role of parents in children's education is very important in laying the foundation of life that determines the good and bad future of the child, all of which depends on the education provided by the family (parents) and society (environment). The family is the smallest unit of a society, an ideal family will create a conducive, pleasant atmosphere in a family. In general, a father and mother have the same role in educating and caring for children. However, there is a slight difference in touch. The touches given by parents in the first 7 years of the child (the Golden Age) will determine the second 7 years and the third 7 years. Therefore, basic Islamic religious education for children begins at the age of 0-6 years by understanding the nature of early childhood itself and providing stimulus (stimulation) according to its development. So, parents can bring out the potential of the child's spiritual nature.